Faktor-Faktor yang Memengaruhi Pendapatan Usahatani Kelapa Sawit Swadaya di Kecamatan Manis Mata Kabupaten Ketapang - Suyatno, Adi; Pramudia, Dinda; Imelda, Imelda (Perkebunan dan Lahan Tropika, 2025)
This research is based on the assumption that several variables play a role in determining and directly influencing the income of independent oil palm farmers operating in Manis Mata sub-district, Ketapang District, an agricultural region dominated by oil palm cultivation. The main objective of this study is to identify the factors contributing to the income of independent oil palm farmers in the area. The research was conducted from December 2024 to January 2025 in Manis Mata sub-district, Ketapang Regency. The approach used was a quantitative descriptive method, with a sample size of 93 independent oil palm farmers. The analysis revealed that land area has a positive and significant impact, confirming that the larger the land ownership, the higher the income per hectare tends to be. Other variables, such as plant age and labor wages, have been shown to have a significant positive effect, so that increasing plant age and labor wages will increase income. Conversely, the prices of KCL fertilizer and herbicide showed a negative and significant impact, indicating that higher input prices will directly reduce farmer income due to the high costs they must bear. Neither the price of NPK fertilizer nor that of TSP fertilizer has a significant impact on income from independent oil palm farming in Manis Mata sub-district, Ketapang District.